8m-(7m+5)=-8-2(m+12)

Simple and best practice solution for 8m-(7m+5)=-8-2(m+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8m-(7m+5)=-8-2(m+12) equation:


Simplifying
8m + -1(7m + 5) = -8 + -2(m + 12)

Reorder the terms:
8m + -1(5 + 7m) = -8 + -2(m + 12)
8m + (5 * -1 + 7m * -1) = -8 + -2(m + 12)
8m + (-5 + -7m) = -8 + -2(m + 12)

Reorder the terms:
-5 + 8m + -7m = -8 + -2(m + 12)

Combine like terms: 8m + -7m = 1m
-5 + 1m = -8 + -2(m + 12)

Reorder the terms:
-5 + 1m = -8 + -2(12 + m)
-5 + 1m = -8 + (12 * -2 + m * -2)
-5 + 1m = -8 + (-24 + -2m)

Combine like terms: -8 + -24 = -32
-5 + 1m = -32 + -2m

Solving
-5 + 1m = -32 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-5 + 1m + 2m = -32 + -2m + 2m

Combine like terms: 1m + 2m = 3m
-5 + 3m = -32 + -2m + 2m

Combine like terms: -2m + 2m = 0
-5 + 3m = -32 + 0
-5 + 3m = -32

Add '5' to each side of the equation.
-5 + 5 + 3m = -32 + 5

Combine like terms: -5 + 5 = 0
0 + 3m = -32 + 5
3m = -32 + 5

Combine like terms: -32 + 5 = -27
3m = -27

Divide each side by '3'.
m = -9

Simplifying
m = -9

See similar equations:

| (2a-3b)(2a-3b)= | | X(x+13)=608 | | X+15=2x-20 | | 2y(6y-5)(3y+2)= | | 8(2-n)-1=n+3(-5n-1)+7n | | 3[x+10]+5=38 | | (4x+3y)(6x-y)= | | (b-2)(3c+2)= | | 68-y=265 | | X-6x-9=6 | | -2a(3a-4b)= | | y=3x^2-8+5 | | -y+76=187 | | 113=236-w | | 5+5(3x+5)=8x+(3x-18) | | 3xy(4x-5xy+2z)= | | 6y-36=6(7y+6) | | 2x^2+7x-1=0 | | 5a-3=11+7a | | 5a-3=11+7 | | (y+1)-(y-9)=2(5y-6)-8y | | -3(-5x-14)=17x+9 | | -2x+5=5x+4 | | 1+2-3+4-5+6-7+8x= | | -u-(5+13u)+10=-6(4u+11)-9 | | x^2-10x-12=0 | | 2+2=xf | | 2+2=f | | 5(-3y-4)+13=11y+7(5-4y) | | p^3+8p^2=18p | | 3(1+5)-3(-8x-7)=-45 | | -12d-16=-2(d+8)-12d |

Equations solver categories